The Silence of Corruption : Identifying Underreporting of Business Corruption through Randomized Response Techniques - Jensen, Nathan M. (2012)
Research on the economic consequences of corruption has been hampered by the inability to directly measure corruption. Using an innovative methodology that allows respondents to report individual experiences with corruption while minimizing self-incrimination and an objective diagnostic to evaluate lying (false responses), this paper explores the extent of business corruption in Bangladesh. The analysis shows that traditional measures of corruption underreport the extent of business corruption in Bangladesh and existing strategies to evaluate and elicit truthful responses have limited effectiveness. The authors identify the types of firms that are associated with false responses and nonresponses to survey questions on corruption.